The greenhouse project. - Lee, Changzhi. (2010)
Final Year Project of Lee Changzhi. Topic dwells on designing experiences and the need to mark milestones in life. With the aid of literary surveys, over fifteen interviews, research into the worlds of spectacles, religious gatherings and birthdays, I built a case that highlights possible patterns in the realms of marking milestones - the 'ups' in life.